Post-radiation effects of core pumped monolithic holmium-doped silica fibre lasers - Theodosiou, Antreas; Koutsokeras, Loukas E.; Ioannou, Andreas; Stancalie, Andrei; Negut, Daniel Constantin; Aubrecht, J.; Peterka, Pavel; Constantinides, Georgios; Kalli, Kyriacos (My University, 2023)
We present our recent studies regarding the influence of ionized radiation when a monolithic Holmium fibre laser was exposed under a total dose of 350 Gy of γ-radiation. Since fibre lasers have many uses for space applications, it is important to study the robustness and the effects caused by ionized radiation. The optical fibre laser was characterized before and after the exposure using spectrum analysis and Raman spectrometry while the variations were quantified. Moreover, the fibre laser response and the FBG mirrors' temperature response were analyzed.
Keywords: doped fibers; fiber lasers; gamma-radiation; holmium doped fiber